The anthropology of morality in Melanesia and beyond (Anthropology and cultural history in Asia and the Indo-Pacific, 2007)
"The Anthropology of Morality in Melanesia and Beyond examines how Melanesians experience and deal with moral dilemmas and challenges. Taking Kenelm Burridge's seminal work as their starting point, the contributors focus upon public situations and types of people that exemplify key ethical contradictions for members of moral communities. While returning to some classical concerns, such as the roles of big men and sorcerers, the book opens new territory with richly textured ethnographic studies and theoretical reviews that explore the interface between the values associated with indigenous village life and the ethical orientations associated with Christianity, the state, the marketplace, and other facets of 'modernity'."--BOOK JACKET.